1985
DOI: 10.3168/jds.s0022-0302(85)81070-5
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Nonreturn Rates of Dairy Bulls to Binding Affinity of Heparin to Sperm

Abstract: The binding of the glycosaminoglycan [3H] heparin to bull spermatozoa was compared with nonreturn rates of dairy bulls. Semen samples from five bulls above and five below an average 71% nonreturn rate were used. Samples consisted of first and second ejaculates on a single day collected 1 d/wk for up to 5 consecutive wk. Saturation binding assays using [3H] heparin were performed to quantitate the binding characteristics of each sample. Scatchard plot analyses indicated a significant difference in the binding a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
1

Year Published

1990
1990
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 16 publications
0
17
0
1
Order By: Relevance
“…Bulls with increased fertility produced sperm with greater affinity to bind heparin-like complex sugars that were commonly found in the reproductive tract of females (Marks and Ax 1985). It has been suggested that seminal proteins mediate the binding of sperm cells to oviductal epithelium and preserve membrane integrity by exerting inhibiting effects on the mitochondrial activity and metabolism to conserve energy needed until fertilization as well as to minimize the production of ROS and LPO of sperm membrane.…”
Section: Ai and Conception Ratementioning
confidence: 99%
“…Bulls with increased fertility produced sperm with greater affinity to bind heparin-like complex sugars that were commonly found in the reproductive tract of females (Marks and Ax 1985). It has been suggested that seminal proteins mediate the binding of sperm cells to oviductal epithelium and preserve membrane integrity by exerting inhibiting effects on the mitochondrial activity and metabolism to conserve energy needed until fertilization as well as to minimize the production of ROS and LPO of sperm membrane.…”
Section: Ai and Conception Ratementioning
confidence: 99%
“…The ability of spermatozoa to bind heparin is also related to fertility. Five bulls with above average fertility produced sperm with higher affinity for heparin than sperm from five bulls with below average fertility (Marks and Ax, 1985). In nine bulls whose relative fertility was determined more accurately by artificial insemination of semen from pairs of the bulls into each cow and blood-typing the offspring to determine the sire, heparin affinity, and the number of binding sites to sperm were also related to fertility (Miller and Ax, 1988).…”
Section: Relationship Between Fertility and The Ability Ofmentioning
confidence: 99%
“…Various functional tests have been applied to sperm including assessment of acrosome reaction induction (Lenz et al, 1988;Parkinson, 1992, 1995;Janskauskas et al, 2000), heparin binding to sperm (Marks and Ax, 1985), sperm-zona binding assays (Fazeli et al, 1993;Zhang et al, 1998), and sperm penetration assays (Ohgoda et al, 1988;Henault and Killian, 1995). Advances in bovine IVF and embryo culture techniques have allowed the relationship between in vivo bull fertility and IVF outcomes to be examined (Hillery et al, 1990;Marquant-Le Guienne et al, 1990;Shamsuddin and Larsson, 1993;Lonergan, 1994;Schneider et al, 1999;Larsson and RodriguezMartinez, 2000).…”
Section: Introductionmentioning
confidence: 99%